1999
DOI: 10.1074/jbc.274.29.20688
|View full text |Cite
|
Sign up to set email alerts
|

Ribonuclease Activity of Rat Liver Perchloric Acid-soluble Protein, a Potent Inhibitor of Protein Synthesis

Abstract: Rat liver perchloric acid-soluble protein (L-PSP) is a potent inhibitor of cell-free protein synthesis; however, its mechanism of action is not known. Here we show that the protein is a unique ribonuclease and that this activity is responsible for the inhibition of translation. The addition of perchloric acid-soluble protein to a rabbit reticulocyte cell-free system at a concentration of 6.2 M led to an almost complete inhibition of protein synthesis. The kinetics are unlike those of hemin-controlled inhibitor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
79
0
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(84 citation statements)
references
References 23 publications
3
79
0
2
Order By: Relevance
“…Among these, two factors, DCP1A and HRSP12, are known to be related to RNA-degrading ability: DCP1A promotes decapping activity of DCP2 (Coller and Parker 2004), and HRSP12 has an endoribonucleolytic ability (Morishita et al 1999). Several previous studies and the present data support the important roles of DCP1A-mediated decapping and HRSP12-mediated endoribonucleolytic cleavage in GMD.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Among these, two factors, DCP1A and HRSP12, are known to be related to RNA-degrading ability: DCP1A promotes decapping activity of DCP2 (Coller and Parker 2004), and HRSP12 has an endoribonucleolytic ability (Morishita et al 1999). Several previous studies and the present data support the important roles of DCP1A-mediated decapping and HRSP12-mediated endoribonucleolytic cleavage in GMD.…”
Section: Discussionsupporting
confidence: 83%
“…and has endoribonuclease activity (Morishita et al 1999;Mistiniene et al 2003Mistiniene et al , 2005. Although it is unknown whether the trimeric structure of HRSP12 is critical for its endoribonucleolytic activity, it is possible that the trimerization of HRSP12 is involved in maintaining the structural integrity of a functionally active GMD complex.…”
Section: The Integrity Of the Gmd Complex Is Necessary For Gmdmentioning
confidence: 99%
“…Studies suggest that UK has multiple functions. For example, UK was reported to inhibit protein synthesis in vitro in rabbit reticulocyte lysate (35). Overexpression of UK suppressed cell proliferation of normal rat kidney epithelial cells without any influence on cell viability (20).…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of UK suppressed cell proliferation of normal rat kidney epithelial cells without any influence on cell viability (20). In addition, UK was reported to act as an endoribonuclease that inhibits translation by cleaving mRNA (35).…”
Section: Discussionmentioning
confidence: 99%
“…RidA belongs to the YjgF/YER057c/UK114 superfamily, which is highly conserved across a wide range of organisms. This protein family has a variety of assigned functions, ranging from translational inhibition and activation of a proteinase, to nuclease and chaperone activity (33)(34)(35)(36). Recent studies identified an enamine/imine deaminase activity of RidA in Salmonella enterica (15).…”
Section: Proteins Modified Upon Peroxynitrite Treatment Are Not Abundmentioning
confidence: 99%